RISK FACTORS OF INCISIONAL HERNIA IN PATIENTS PRESENTING TO TERTIARY CARE HOSPITAL - ULLAH, Z; KHAN, MA; ZARIN, MA; BIBI, B; KHALIL, HG; KHURSHID, A (Biological and Clinical Sciences Research Journal, 2024)
Incisional hernia is a common complication following abdominal surgeries, influenced by various demographic and clinical factors. Identifying associated risk factors can aid in preventive strategies and improve surgical outcomes. Objective: To assess the associated risk factors in patients presenting to tertiary care hospital. Methods: This study was carried out from March 2023 to March 2024, involving 150 patients aged 30 years or older, who underwent either laparotomy or laparoscopy for abdominal surgeries. Data were collected from medical records and postoperative follow-ups, focusing on demographic characteristics, comorbidities, surgical data, and the development of incisional hernia and its associated risk factors. Results: The incidence of incisional hernia was 12.7%, with 68.4% of affected patients being over the age of 45. Risk factors identified included obesity (57.9%) of obese patients developed incisional hernia), diabetes (52.6%), hypertension (63.2%), and laparotomy (89.5% of laparotomy patients developed hernia). Wound infections were also considerably associated with incisional hernia development (36.8%). Conclusion: The study identified age, obesity, diabetes, hypertension, laparotomy, and wound infections as notable risk factors for the development of incisional hernia.